Strategi Implementasi Kebijakan Bangunan Gedung Hijau Di Kota Bandung - Syaiful Iman; Edah Jubaedah; Baban Sobandi (Jurnal Media Administrasi Terapan, 2021)
This study aims to analyze the implementation of green building policies and formulate a strategy for implementing policies on green buildings in the city of Bandung. Bandung Mayor Regulation Number 1023 of 2016 concerning Green Building can be divided into three policy stages, including the pre-construction stage, the construction stage and the post-construction stage. In its implementation, the three stages have not been fully implemented so that it can be said that it is not optimal. This study uses qualitative research methods, the implementation of green building policies in the city of Bandung is analyzed through communication factors, resources, disposition and bureaucratic structure factors. The results show that the implementation of green building policies in the city of Bandung is determined by factors of communication, resources, disposition and bureaucratic structure factors. Judging from the factors implementing the green building policy in Bandung City, a strategy that can be developed to improve it is the Turn Around strategy (repair and change). Priority strategies that can be developed are: Increasing the intensity of outreach to the community through cooperation with regional agencies; Increasing training standards that must be followed by policy implementers in collaboration with training institutions; Placement of staff according to educational qualifications in order to improve implementation performance to achieve environmentally sound building arrangements; Preparation of SOPs for the construction stage and post-construction stage through collaboration with academics.